1993
DOI: 10.1111/1467-9566.ep10490713
|View full text |Cite
|
Sign up to set email alerts
|

All in the family: social processes in ovarian egg donation between sisters

Abstract: Interviews and participant observation were conducted at a US infertility clinic with women who were attempting to become pregnant with eggs donated by their biological sisters. Sisters who donated eggs were also followed and interviewed regarding their experiences, as were a number of husbands of recipients. Five significant social processes characterising the sisters' passage through egg donation are discussed: (1) negotiating dissimilar treatment experiences, (2) communicating cautiously, (3) interacting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 33 publications
(29 reference statements)
2
24
0
Order By: Relevance
“…In the early days of IVF egg donors tended to be known. Some US fertility experts advocated sister-to-sister donation rather than anonymous donation (Lessor, 1993). Studies at that time reported positive attitudes towards egg donation by sisters among infertile couples (Sauer, 1988) and the broader public (Lessor, et al, 1990).…”
Section: Challenges In Intra-family Donation Ejjy Vayena and Susan Gomentioning
confidence: 99%
See 2 more Smart Citations
“…In the early days of IVF egg donors tended to be known. Some US fertility experts advocated sister-to-sister donation rather than anonymous donation (Lessor, 1993). Studies at that time reported positive attitudes towards egg donation by sisters among infertile couples (Sauer, 1988) and the broader public (Lessor, et al, 1990).…”
Section: Challenges In Intra-family Donation Ejjy Vayena and Susan Gomentioning
confidence: 99%
“…The perceived importance of motherhood and coming frmn a large family wer e also reported as reasons to donate (Warren and Blood, 2003). In intergenerational donation, similarly there is a strong sense of helping the parent or child, and of providing a 'gift from the heart' (Lessor, 1993;Nikolettos er al., 2003;Winter and Daniluk, 2004).…”
Section: Reasons For Intra-familial Donationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increasing reliance on altruistic oocyte donation in some jurisdictions due to legal prohibitions on donor compensation, and patients' preference in using a known donor for pragmatic or personal reasons (Khamsi, Endman, Lacanna, & Wong, 1997;Lessor, 1993;Winter & Daniluk, 2004), relatively few studies have reported the experiences of altruistic known donors during or following donation. Most are found among studies that include a subset of altruistic known donors among other types of donors in the study population (Baetens, Devroey, Camus, van Steirteghem, & Ponjaert-Kristoffersen, 2000;Fielding, Handley, Duqueno, Weaver, & Lui, 1998;Greenfeld, Mazure, Olive, & Keefe, 1995;Kirkland et al, 1992;Sauer & Paulson, 1992;Weil, Cornet, Sibony, Mandelbaum, & Salat-Baroux, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Most are found among studies that include a subset of altruistic known donors among other types of donors in the study population (Baetens, Devroey, Camus, van Steirteghem, & Ponjaert-Kristoffersen, 2000;Fielding, Handley, Duqueno, Weaver, & Lui, 1998;Greenfeld, Mazure, Olive, & Keefe, 1995;Kirkland et al, 1992;Sauer & Paulson, 1992;Weil, Cornet, Sibony, Mandelbaum, & Salat-Baroux, 1994). In-depth accounts of known donors' experiences are found in two studies only (Lessor, 1993;Winter & Daniluk, 2004). These limited empirical data have found that altruistic donors are primarily empathically motivated to help a recipient with whom they have a relationship to achieve their parenting aspirations.…”
Section: Introductionmentioning
confidence: 99%